Spa Service Quality: The Case of the Andaman Tourism Cluster (Phuket, Phang Nga and Krabi), Thailand / Ratthasak Boonyarit and Kullada Phetvaroon - Boonyarit, Ratthasak; Phetvaroon, Kullada (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2011)
The aim of this study was to assess the Service Quality of Spas in the Andaman Tourism Cluster, Thailand. Data were collected from 430 spa customers who had used spa services at Day Spas or Hotel & Resort Spas in the Andaman Tourism Cluster. The objectives were to identify the characteristics of spa customers in the Andaman Tourism Cluster and to investigate the performance areas of service quality at spas in the Cluster by using the IPA Grid. There were 33 service quality attributes identified by using an IPA grid that displayed the results; no-attributes were located in Quadrant 1 (high importance, low performance), 15 attributes were located in Quadrant 2 (both importance and performance are high), 12 attributes were located in Quadrant 3 (both importance and performance are low), and 6 attributes were located in Quadrant 4 (low importance, high performance). In the Andaman Tourism Cluster, the high importance factors of the spa customer concerns were safety, security, cleanliness, and prompt service. Spa customers were highly satisfied with cleanliness, staff attentiveness, atmosphere, as well as staff courtesy. To maintain a competitive position in the Andaman Tourism Cluster and to maintain its status as the Spa Capital of Asia, some recommendations for further research have been suggested.